1993
DOI: 10.3138/m6h4-1006-6422-h744
|View full text |Cite
|
Sign up to set email alerts
|

Consensus or Confusion: Cartographers' Knowledge of Generalization

Abstract: health sciences, history THE CANADIAN HISTORICAL REVIEW utpjournals.press/chr Offering a comprehensive analysis on the events that have shaped Canada, CHR publishes articles that examine Canadian history from both a multicultural and multidisciplinary perspective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Deep knowledge is more important and much more complex to automate and is used by cartographers when superficial knowledge does not suffice. Rieger and Coulson (1993) carried out a survey among a group of cartographers performing interactive generalisation and found that the classification of generalisation operators differs depending on the specific cartographer. Additionally, they discovered that a consensus on such a classification does not exist.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Deep knowledge is more important and much more complex to automate and is used by cartographers when superficial knowledge does not suffice. Rieger and Coulson (1993) carried out a survey among a group of cartographers performing interactive generalisation and found that the classification of generalisation operators differs depending on the specific cartographer. Additionally, they discovered that a consensus on such a classification does not exist.…”
Section: Literature Reviewmentioning
confidence: 99%
“…When two cartographers are given the same generalisation rules for the same area, they will come to different results (Rieger and Coulson, 1993). Exceptions are common in the generalisation process, and there may be more than one ideal generalisation solution.…”
Section: Necessary Research To Improve Current Generalisation Practicementioning
confidence: 99%
“…This knowledge can be acquired thanks to domain experts -but this raises the problem of collecting and formalising it (Rieger and Coulson 1993, Weibel et al 1995, Kilpelinen 2000) -a problem classically known as 'the bottleneck of knowledge acquisition' (Feigenbaum 1977). One approach for solving this dilemma is the application of Machine Learning Techniques.…”
Section: Related Workmentioning
confidence: 99%
“…Unfortunately, no consensus has yet been reached on an all-encompassing set of operators. Even worse, authors may use different definitions for the same term or use different terms for the same definition, as a recent study by Rieger and Coulson (1993) has shown.…”
Section: A Closer Look At Generalization Operatorsmentioning
confidence: 99%